59.8k views
3 votes
Simplify (x^4y)^3.
x^12y^3
x^4y^3
x^7y^3

User Johnbot
by
5.5k points

1 Answer

3 votes

Answer: Choice A, x^12y^3

=========================================================

Step-by-step explanation:

Think of x^4y as x^4y^1. When we raise this to the third power, we multiply the outer exponent 3 by each inner exponent

x^4 turns into x^12

y^1 turns into y^3

-----------

This is one way to show your work

(x^4y)^3

(x^4y^1)^3

x^(4*3)*y^(1*3) ... multiplying outer exponent by each inner exponent

x^12y^3

-----------

A more lengthy way to get the answer is to write x^4y out three times multiplying by itself that many times. The outer exponent 3 tells us we will have three copies of x^4y multiplied with itself.

(x^4y)^3 = (x^4y)*(x^4y)*(x^4y)

(x^4y)^3 = (x^4*x^4*x^4)*(y*y*y)

(x^4y)^3 = ( x^(4+4+4) ) * ( y^(1+1+1) )

(x^4y)^3 = x^12y^3

User Nic Scozzaro
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.